Cross-cultural adaptation of the Child and Adolescent Symptom Inventory-5 (CASI-5) for use in central and south-western Uganda: the CHAKA project. (October 2017) - Mpango, Richard Stephen; Kinyanda, Eugene; Rukundo, Godfrey Zari; Gadow, Kenneth D.; Patel, Vikram
Our study was to examine the applicability of translating and culturally adapting the Child and Adolescent Symptom Inventory-5 (CASI-5) for use in Uganda. This process followed guidelines recommended by the International Test Commission. A number of the CASI-5 concepts needed to be revised to capture the idioms for emotional, behavioural disorders and individual functioning among children and adolescents in Uganda. Our experience is that before introduction into another culture, psychological assessment instruments should undergo an adaptation process such as as the one used.